A systematic literature review and bibliometric analysis of education for sustainable development integration in science education and its unaddressed gaps - Jiantika Rahmawati; Mohammad Masykuri; Suryadi Budi Utomo (Journal of Environment and Sustainability Education, 2025)
Education for Sustainable Development (ESD) is an important approach to preparing younger generations to face global challenges such as environmental, social, and economic crises. Integrating ESD into science instruction is crucial because science provides the conceptual foundations and critical thinking skills needed to understand sustainability issues. Despite growing attention, implementation remains uneven and the literature is imbalanced across region, levels, and designs. This study examines trends, focus, and research gaps related to ESD in science education through a Systematic Literature Review (SLR) combined with bibliometric analysis. Data were obtained from the Scopus database using the keywords “education for sustainable development” and “science education,” which yielded 81 articles published between 2015-2025 and 46 articles were deemed eligible for analysis. Beyond thematic synthesis, the bibliometric maps reveal the field’s structure, temporal dynamics, and the peripheral positioning of several ESD integrations within science classrooms. The SLR results indicate that research on ESD in science education is dominated by qualitative studies focusing on environmental awareness and sustainable attitudes, leaving a limited evidence base to estimate causal impacts on science competencies and 21st century skills. There are gaps in the development of innovative ESD-based learning models, particularly at the elementary and secondary levels, as well as limitations in measuring 21st-century skills integrated with ESD principles. These findings highlight the need for further exploration of effective and contextual pedagogical approaches to implementing ESD in science education. Methodologically, the concurrent use of SLR and bibliometrics still uncommon in science education to adds depth and enhances interpretive validity.